2014
DOI: 10.1017/thg.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Multiple Maternities in Triplet Families

Abstract: In earlier studies, scientists have attempted to identify genetic and environmental factors affecting the rate of multiple maternities among humans. We contribute to these studies by analysing the frequencies of multiple maternities in sibships containing triplets. Use of the Hellin transformation is included in evaluation of the triplet rate. Our results indicate greater frequencies of repeated multiple maternities in the sibships than expected, based on population frequencies. The excesses obtained are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…would not seem to be responsible for this secondary split. It has been suggested that this type of MZ twinning could be related to a uterine, endometrial, or early pregnancy factor somehow playing a role in increasing the likelihood for this secondary MZ twin split to occur around the time of implantation (Aston et al, 2008; Burton et al, 2007; Choux et al, 2015; Fellman & Eriksson, 2014; Fennessy et al, 2015; Gray et al, 2001; Guilherme et al, 2008; James et al, 2012; Klein et al, 2006; Sklar et al, 2017; Yovich et al, 1984). In addition, when two ova “appear” in the uterus, one may already be “overripe,” therefore being at risk for ova splitting.…”
Section: Mechanism(s) Of Mz Twinningmentioning
confidence: 99%
“…would not seem to be responsible for this secondary split. It has been suggested that this type of MZ twinning could be related to a uterine, endometrial, or early pregnancy factor somehow playing a role in increasing the likelihood for this secondary MZ twin split to occur around the time of implantation (Aston et al, 2008; Burton et al, 2007; Choux et al, 2015; Fellman & Eriksson, 2014; Fennessy et al, 2015; Gray et al, 2001; Guilherme et al, 2008; James et al, 2012; Klein et al, 2006; Sklar et al, 2017; Yovich et al, 1984). In addition, when two ova “appear” in the uterus, one may already be “overripe,” therefore being at risk for ova splitting.…”
Section: Mechanism(s) Of Mz Twinningmentioning
confidence: 99%